Soybean yield and water productivity gaps associate with ENSO-dependent effects of fungicide, sowing date and maturity group - Videla Mensegue, Horacio Rogelio (2024)
Context: Soybean, the focus of this study, is the most widely sown crop and the main source of external income in Argentina. The reported soybean yield gap calculated as the difference between water-limited potential yield (Yw) and actual on-farm yield in the Argentinean Pampas averaged 1260 kg ha−1 or 32% of Yw. Actual water productivity (the ratio between actual yield and water use), the upper limit of water productivity (WPw), and the water productivity gap (WPg) have not been quantified, and their relationships with yield gap are unknown. Objectives: i) benchmark water-limited potential yield and the upper limit of water productivity and ii) identify the primary factors and their interactions with ENSO (El Niño Southern Oscillation) phases driving variations in yield- and water productivity gaps. Methods: We compiled a data set from 3692 rainfed soybean crops including actual yield, water supply (available soil water at sowing + seasonal rainfall), actual water productivity, WPw, and Yg and WPg. Then, we identified the environmental and agronomic factors underlying yield and water productivity gaps, and their relations with ENSO phase. Results and conclusions: Yield gap averaged 1.63 t ha−1 or 32% of Yw and WPg averaged 2.24 kg ha−1 mm−1 or 33% of WPw. Agronomic factors, including phosphorus fertilization, fungicide application, sowing date, soybean maturity group and plant density collectively explained 61% of the variation in yield gap. Environmental factors explained 55% of the variation in the water productivity gap; water supply, rainfall before the crop cycle, presence of water table, phosphorus fertilization, fungicide application and sowing date were the most important factors. Both Yg and WPg varied with interactions between ENSO phase and fungicide application, sowing date, and maturity group. For example, fungicide application reduced the water productivity gap up to 41% (0.98 kg ha−1 mm−1) under El Niño with no effect of fungicide in the Neutral phase. Significance: Both yield and water productivity gaps featured interactions between ENSO phase and fungicide application, sowing date, and maturity group, which suggest opportunities to use weather forecasts to inform management decisions.